High-sealing damping aluminum electrolytic capacitor and processing technology thereof

By using sealing plugs and cushions made of silicone rubber material, the problem of insufficient sealing performance of aluminum electrolytic capacitors under extreme conditions is solved, and higher seal stability and shock absorption performance are achieved, ensuring the reliability and service life of the capacitor.

CN120072529APending Publication Date: 2025-05-30DONGGUAN YONGQUAN ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510243806.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

In the extreme conditions such as high humidity, high temperature, vibration and impact, existing aluminum electrolytic capacitors are difficult to completely prevent the invasion of dust, moisture and corrosive gases, resulting in changes in internal chemical composition and corrosion of metal components, affecting the working reliability and service life of the capacitor.

Method used

The sealing plug and cushion made of silicone rubber material prevents dust, moisture and corrosive gases from entering the inside of the capacitor through its excellent sealing and shock absorption. Silicone rubber materials are characterized by high temperature resistance, good weather resistance, aging and impact resistance, and can maintain stable performance in harsh environments.

Benefits of technology

It significantly improves the seal stability inside the capacitor, prevents external factors from intrusion, ensures reliability and use safety in harsh environments, and enhances the shock absorption performance of the capacitor and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072529A_ABST
    Figure CN120072529A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electronic components, in particular to a high-sealing damping aluminum electrolytic capacitor and a processing technology thereof. Comprising an aluminum shell, an element, a sealing plug and a cushion, the element is contained in the aluminum shell, the element is sealed in the aluminum shell through the sealing plug, the end of the element is provided with two leads in an extending mode, the sealing plug is provided with first through holes for the leads to penetrate through, each lead is provided with a terminal in an extending mode, the terminals extend to the outer surface of a sealing piece, and the cushion is arranged on the sealing piece. The seat cushion is installed at the opening of the aluminum shell and seals the sealing plug, the seat cushion is provided with a second through hole for the terminal to pass through, and the sealing plug and the seat cushion are both made of silicon rubber materials. According to the capacitor, the seat cushion is arranged, and the sealing plug and the seat cushion are made of silicone rubber materials, so that the sealing stability in the capacitor can be enhanced, and the stability of the terminals can be ensured, and therefore, the reliability and the use safety of the capacitor in severe environments such as high humidity, high temperature, vibration and impact can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic components, and more specifically, to a highly sealed and shock-absorbing aluminum electrolytic capacitor and its processing technology. Background Art

[0002] As a common energy storage component, aluminum electrolytic capacitors are widely used in various electronic devices. It mainly consists of an aluminum cylinder (negative electrode), a liquid electrolyte, a bent aluminum strip (positive electrode), etc., and a layer of oxide film is formed on the positive electrode plate as a dielectric through DC voltage treatment. This structure makes aluminum electrolytic capacitors have advantages such as large capacitance and low cost, so they are widely used in fields such as consumer electronics, household appliances, industrial control, and communication equipment. However, with the progress of technology and the diversification of application environments, especially the requirements for capacitors in new energy vehicles and intelligent connected vehicle electronic systems are getting higher and higher.

[0003] To address these challenges, existing technical means mainly include improving the electrolyte formula, optimizing the shell material, and enhancing the sealing performance. For example, adding high-temperature resistant additives to improve the thermal stability of the electrolyte; selecting higher-strength aluminum alloy materials to make the shell to enhance mechanical strength; using multi-layer composite materials or special coatings to improve the moisture-proof and corrosion-proof capabilities of the capacitor. In addition, some designs also introduce additional sealing measures, such as using epoxy resin potting or adding an external protective cover to reduce the influence of external environmental factors.

[0004] Although the above methods have improved the performance of aluminum electrolytic capacitors to a certain extent, there are still certain limitations under extreme conditions such as high humidity, high temperature, vibration, and shock. Especially when the capacitor is in such an environment for a long time, the sealing material is difficult to completely prevent the intrusion of dust, moisture, and corrosive gases, which will not only cause changes in the internal chemical composition of the capacitor, but also accelerate the corrosion of metal components, ultimately affecting the working reliability and service life of the capacitor. Therefore, how to further improve the sealing and shock-absorbing performance of the capacitor has become a key problem to be solved urgently. Summary of the Invention

[0005] In order to improve the sealing performance and buffering performance of electrolytic capacitors, the present application provides a highly sealed and shock-absorbing aluminum electrolytic capacitor and its processing technology.

[0006] In a first aspect, the present application provides a highly sealed shock-absorbing aluminum electrolytic capacitor, which adopts the following technical solutions: It includes an aluminum shell, an element, a sealing plug, and a cushion. The element is accommodated inside the aluminum shell, the sealing plug seals the element in the aluminum shell. Two leads are extended and provided at the end of the element. The sealing plug is provided with a first through hole for each lead to pass through. Each lead is extended and provided with a terminal, and the terminal extends to the outer surface of the sealing member. The cushion is installed at the opening of the aluminum shell and seals the sealing plug. The cushion is provided with a second through hole for the terminal to pass through. Both the sealing plug and the cushion are made of silicone rubber material.

[0007] By adopting the above technical solutions, by utilizing the excellent sealing and shock-absorbing properties of the silicone rubber material, it can effectively prevent dust, moisture, and corrosive gases from entering the interior of the capacitor. This material not only has excellent sealing performance and can fit various smooth surface materials, but also has the characteristics of high temperature resistance, good weather resistance, anti-aging, and impact resistance, and can maintain stable performance in harsh environments. Therefore, by using the sealing plug and the cushion made of silicone rubber material, it can not only enhance the sealing stability inside the capacitor, but also ensure the stability of the terminals, thereby improving the reliability and use safety of the capacitor in harsh environments such as high humidity, high temperature, vibration, and impact.

[0008] Preferably, the element is sequentially provided with a first electrolytic paper, an anode foil, a second electrolytic paper, and a cathode foil from the outer layer to the inner layer. During the winding process, the first electrolytic paper, the anode foil, the second electrolytic paper, and the cathode foil wrap the leads to form the element. The first electrolytic paper abuts against the inner wall of the aluminum shell. One lead is located between the anode foil and the second electrolytic paper, and the other lead is located between the cathode foil and the first electrolytic paper.

[0009] By adopting the above technical solutions, the multi-layer structure design of the element can be stably sealed inside the aluminum shell, avoiding scattering due to factors such as vibration and impact, thereby ensuring the structural stability of the capacitor. Specifically, the first electrolytic paper abuts against the inner wall of the aluminum shell, which can effectively reduce the influence of the external environment on the capacitor and improve its sealing performance and reliability.

[0010] Preferably, the element further includes an electrolyte, and the electrolyte adheres to the surfaces of the first electrolytic paper, the anode foil, the second electrolytic paper, the cathode foil, and the leads.

[0011] By adopting the above technical solution, the electrolyte adheres to the surfaces of the first electrolytic paper, the anode foil, the second electrolytic paper, the cathode foil, and the lead wires, which can ensure good contact between the components of the capacitor, improve the conductivity and stability, and thus guarantee the capacitance, loss, lifespan, and stability of the capacitor. In addition, the presence of the electrolyte can further enhance the structural stability of the element, avoid scattering phenomena caused by factors such as vibration and impact, and improve the overall reliability and service life of the capacitor.

[0012] Preferably, the silicone rubber material is composed of raw materials including the following weight percentages: Vinyl raw rubber 48 - 62% Hydrogen-containing silicone oil 5 - 8% Hydroxy silicone oil 10 - 20% Acryloxy group-containing silane 1 - 5% Fumed silica 10 - 23% Expandable graphite 0.5 - 2.3% The balance is vulcanizing agent.

[0013] By adopting the above technical solution, vinyl raw rubber endows the silicone rubber material with good high-temperature resistance and flexibility. The hydrogen-containing silicone oil and hydroxy silicone oil react with it further to enhance its performance. Fumed silica plays a role in filling and reinforcing, improving the mechanical strength and wear resistance of the material. Expandable graphite can expand rapidly at a specific temperature, further enhancing the sealing effect of the sealing plug and the seat cushion. The vulcanizing agent promotes the cross-linking reaction between the components, ensuring the stability and durability of the final product. In summary, this silicone rubber material has excellent sealing and shock-absorbing properties and can maintain reliable capacitor performance in harsh environments such as high temperature, high humidity, and vibration.

[0014] Preferably, the acryloxy group-containing silane is composed of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and (3-acryloxypropyl)tris(trimethylsiloxy)silane.

[0015] By adopting the above technical solution, the compounding of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and (3-acryloxypropyl)tris(trimethylsiloxy)silane can further improve the comprehensive performance of the silicone rubber material. These two compounds contain acryloxypropyl and methacryloxypropyl respectively. When compounded, they can cooperate with each other to enhance the high-temperature resistance, flexibility, and mechanical strength of the silicone rubber material. In addition, this compounding can also improve the compatibility of expandable graphite and fumed silica in the silicone rubber raw material system, making these fillers more evenly distributed in the silicone rubber, thereby further enhancing its sealing and shock-absorbing properties.

[0016] Preferably, the expandable graphite is insulating modified expandable graphite, and the insulating modified expandable graphite is composed of the following raw materials in weight percentages: Organosilicon-modified polyurethane emulsion 5-8% Expandable graphite 40-65% Benzoyl peroxide 0.1-0.5% 2,3'-Diallylbisphenol A 0.1-1.3% Glycidyl ether oxypropyl cyclotetrasiloxane 1-3% Methacryloylethyl sulfobetaine 0.1-0.8% The balance is diethylene glycol methyl ethyl ether.

[0017] By adopting the above technical solution, the insulating modified expandable graphite has improved film-forming stability, corrosion resistance and flexibility under the action of the organosilicon-modified polyurethane emulsion. 2,3'-Diallylbisphenol A, glycidyl ether oxypropyl cyclotetrasiloxane and methacryloylethyl sulfobetaine form a macromolecular copolymer under the initiation of benzoyl peroxide, further enhancing its comprehensive performance. These improvements make the insulating modified expandable graphite easier to disperse evenly in the silicone rubber raw material system, enhance the sealing and shock-absorbing performance of the capacitor, thus effectively preventing dust, moisture and corrosive gases from entering the interior of the capacitor and ensuring reliability and safety in harsh environments.

[0018] Preferably, the insulating modified expandable graphite is prepared by the following method: Calculated by weight percentage, benzoyl peroxide, 2,3'-diallylbisphenol A, glycidyl ether oxypropyl cyclotetrasiloxane, methacryloylethyl sulfobetaine and diethylene glycol methyl ethyl ether are mixed evenly, added to 60-68 °C, reacted for 1-2 h, then the organosilicon-modified polyurethane emulsion is added, mixed evenly, then expandable graphite is added, mixed evenly, distilled under reduced pressure to remove the solvent, dried, crushed, and sieved to obtain the insulating modified expandable graphite.

[0019] By adopting the above technical solution, the preparation method of the insulating modified expandable graphite can ensure that each component reacts fully to form a stable coating film. Specifically: Benzoyl peroxide is used as an initiator to promote the polymerization reaction between 2,3'-diallyl bisphenol A, glycidyl ether oxypropyl cyclotetrasiloxane and methacryloylethyl sulfobetaine, generating a macromolecular copolymer. The macromolecular copolymer acts synergistically with the silicone-modified polyurethane emulsion to improve the overall properties of the material, including film-forming stability, corrosion resistance and flexibility. Expandable graphite is evenly dispersed during the reaction process, and a coating film is formed on its surface, enhancing its compatibility and dispersibility in the silicone rubber raw material system. The finally obtained insulating modified expandable graphite not only has good insulating properties, but also can rapidly expand at high temperatures, further improving the sealing effect of the sealing plug and the cushion, ensuring the reliability and safety of the capacitor in harsh environments.

[0020] Preferably, the silicone rubber material is prepared by the following method: By weight percentage, acryloxy group-containing silane and expandable graphite are weighed and mixed evenly to obtain mixture A; vinyl raw rubber, hydrogen-containing silicone oil and hydroxy silicone oil are weighed and mixed evenly, then heating is started, fumed silica is added, and the mixture is mixed evenly. The mixture is heated to 125 - 135 °C and reacted for 20 - 30 min, then mixture A is added, and the mixture is mixed evenly. Then it is heated to 150 - 165 °C and reacted for 2 - 4 h, cooled to 45 - 55 °C, rubber is kneaded, and filtered to obtain a mixed rubber; a vulcanizing agent is added to the mixed rubber and kneaded to make the vulcanizing agent evenly dispersed in the mixed rubber, obtaining the silicone rubber material.

[0021] By adopting the above technical solution, the preparation method of the silicone rubber material enables each component to be fully mixed evenly. Especially the premixing of acryloxy group-containing silane and expandable graphite further improves the overall properties of the material. The intermediate product generated by the reaction of vinyl raw rubber, hydrogen-containing silicone oil and hydroxy silicone oil at high temperature enhances the basic properties of the silicone rubber. The addition of fumed silica not only plays a reinforcing role, but also improves the fluidity and processing performance of the material. The finally obtained silicone rubber material has excellent high-temperature resistance, shock absorption and sealing properties, can effectively prevent the leakage and damage of the capacitor in harsh environments, and improves its reliability and service life.

[0022] In the second aspect, a production process of a high-sealing shock-absorbing aluminum electrolytic capacitor includes the following steps: Step 1: Stack the first electrolytic paper, anode foil, second electrolytic paper and cathode foil in sequence, and carry out winding. During the winding process, the lead is wound, and then impregnated with electrolyte to obtain an element; the silicone rubber material is put into a mold and then vulcanized and formed to obtain a sealing plug and a cushion.

[0023] By adopting the above technical solution, this production process can realize the efficient production of high-sealing shock-absorbing aluminum electrolytic capacitors. Specifically: The process of stacking the first electrolytic paper, anode foil, second electrolytic paper, and cathode foil in sequence and winding them ensures the close contact and uniform distribution among the layers of materials inside the element, improving the structural stability and electrical performance of the capacitor.

[0024] During the winding process, the lead is coated, enabling the lead to be tightly bonded to each layer of material, enhancing the fixing effect of the lead, avoiding the loosening or breaking of the lead caused by vibration or impact, and improving the overall reliability of the capacitor.

[0025] The element formed after impregnating with the electrolyte not only has good conductivity and stability but also can maintain stable electrical performance during long-term use, extending the service life of the capacitor.

[0026] The silicone rubber material is prepared through a specific formula and process, possessing excellent sealing and shock-absorbing properties. It can effectively prevent dust, moisture, and corrosive gases from entering the interior of the capacitor, ensuring the reliable operation of the capacitor in a harsh environment.

[0027] The obtained sealing plug and cushion are installed at the opening of the aluminum shell, further strengthening the sealing effect of the capacitor and ensuring its safety and stability during long-term use.

[0028] In summary, through optimizing the operation steps and technical parameters of each link, this production process realizes the high-quality production and wide application of high-sealing shock-absorbing aluminum electrolytic capacitors.

[0029] Step 2: Place the element in the aluminum shell, then seal the aluminum shell with the sealing plug, and the lead in the element passes through the first through-hole of the sealing plug to seal the element. Install the cushion at the opening of the aluminum shell, so that the sealing plug is sealed inside the aluminum shell, and the terminal extending from the lead passes through the cushion to obtain a high-sealing shock-absorbing aluminum electrolytic capacitor.

[0030] By adopting the above technical solution, the efficient assembly of high-sealing shock-absorbing aluminum electrolytic capacitors is realized. First, placing the element in the aluminum shell ensures the stability and integrity of the internal structure. Second, using the sealing plug to block the opening of the aluminum shell and enabling the lead to pass through the first through-hole of the sealing plug effectively prevents the intrusion of external impurities and moisture, enhancing the sealing performance of the capacitor. Third, installing the cushion at the opening of the aluminum shell to make it closely abut against the sealing plug further improves the sealing effect and ensures the reliability and safety of the capacitor in a harsh environment. Finally, the terminal extending from the lead passes through the cushion, ensuring the stability of the electrical connection and enabling the entire capacitor to possess excellent mechanical strength and electrical performance.

[0031] Preferably, the step 2 further includes performing a thermal expansion treatment, specifically as follows: Place the element in the aluminum shell, then seal the aluminum shell with a sealing plug, and the lead wire in the element passes through the first through hole of the sealing plug to seal the element. Install the cushion on the opening of the aluminum shell, so that the sealing plug is sealed inside the aluminum shell, and the terminal extended by the lead wire passes through the cushion to obtain a capacitor. Perform thermal expansion at 200 - 210 °C for 0.1 - 1 s to obtain a high-sealing shock-absorbing aluminum electrolytic capacitor.

[0032] By adopting the above technical solution, the capacitor can be thermally expanded at 200 - 210 °C, enabling the expandable graphite in the sealing plug and the cushion to expand instantaneously, thereby further increasing the volume of the sealing plug and the cushion, making the seal between them and the aluminum shell tighter. This treatment not only enhances the overall sealing performance of the capacitor but also improves its performance in harsh environments such as high humidity, high temperature, vibration, and shock. The aluminum shell of this application uses high-temperature-resistant aluminum plate, and its temperature tolerance range is 300 °C to 500 °C; the electrolyte is also a high-temperature-resistant electrolyte; when at 200 - 210 °C, the expandable graphite will expand instantaneously when reaching 200 - 210 °C, thereby increasing the volume of the sealing plug and the cushion and making the seal tighter. The expansion multiple of the expandable graphite is 10 - 30 times. Under the thermal expansion time, temperature, and the amount of expandable graphite used in this application, it will expand and improve the sealing effect.

[0033] Generally, the operating temperature range of electrolytic capacitors is generally between -40 °C and 105 °C, while the highest operating temperature of high-temperature-resistant electrolytic capacitors can reach 150 °C. The expandable graphite in this application will expand slightly when heated during vulcanization molding. The product after this expansion is polished, etc. to form a suitable sealing plug and cushion. When at 200 - 210 °C, the expandable graphite will further expand, and its expansion multiple is 10 - 20 times. This makes the installed sealing plug and cushion tighter, and has better reliability and service life under good performance.

[0034] In summary, this application includes at least one of the following beneficial technical effects: 1. By using a sealing plug and a cushion made of silicone rubber material, the sealing stability inside the capacitor can be significantly improved, effectively preventing dust, moisture, and corrosive gases from entering the capacitor, ensuring reliability and use safety in harsh environments.

[0035] 2. The silicone rubber material has excellent shock-absorbing performance, can keep the structure of the capacitor stable under high vibration and impact conditions, reduce the loosening or damage of internal components caused by external vibration, and extend the service life of the capacitor.

[0036] 3. The combined design of the sealing plug and the cushion not only improves the overall sealing effect but also ensures the stable connection of the lead terminals, further enhancing the overall performance and reliability of the capacitor. Description of the Drawings

[0037] Figure 1 It is a schematic diagram of the explosion structure of a highly sealed and shock-absorbing aluminum electrolytic capacitor of the present application; Figure 2 Schematic diagram of the structure of a highly sealed and shock-absorbing aluminum electrolytic capacitor of the present application; Figure 3 It is a schematic diagram of the winding structure of the element in Step 1; Figure 4 It is the impregnation process of the element in Step 1.

[0038] Explanation of reference numerals: 1. Aluminum shell; 2. Element; 21. Lead wire; 211. Terminal; 22. First electrolytic paper; 23. Anode foil; 24. Second electrolytic paper; 25. Cathode foil; 3. Sealing plug; 31. First through hole; 4. Cushion; 41. Second through hole. Detailed implementation manners

[0039] The following further describes the present application in detail with reference to the Figures 1-4 accompanying drawings and embodiments.

[0040] Description of some raw materials: The vinyl raw rubber is methylphenylvinyl silicone rubber, with a phenyl content (Ph / Si) of 5 - 40; the molecular weight (Mw) is 400,000 - 800,000, and the vinyl content is 0.16 - 0.23%; The hydrogen content of the hydrogen-containing silicone oil is 1.3 - 2.8%, and the viscosity-average molecular weight is between 1000 - 1000; The hydroxyl silicone oil is α-hydrogen-ω-hydroxy-polydimethylsiloxane, CAS No.: 70131-67-8; The particle size of the expandable graphite is 3000 - 4000 mesh; The silicone-modified polyurethane emulsion is Evonik SILIKOPUR silicone-modified polyurethane (PU) emulsion 8081; The vulcanizing agent is bis(2,5-dimethyl-2,5-di(t-butylperoxy)hexane).

[0041] Preparation example of insulating modified expandable graphite Preparation example 1 An insulating modified expandable graphite is prepared by the following method: According to the weight percentage of the insulating modified expandable graphite, 0.1% benzoyl peroxide, 1.3% 2,3'-diallylbisphenol A, 3% glycidoxypropylcyclotetrasiloxane, 0.1% methacryloylethylsulfobetaine, and 50.5% diethylene glycol methyl ethyl ether were mixed evenly, and a preliminary heating reaction was carried out. Then, 5% organosilicon-modified polyurethane emulsion was added and mixed evenly. Next, 40% expandable graphite was added and mixed evenly. Then, vacuum distillation was carried out to remove water and diethylene glycol methyl ethyl ether. It was dried in an oven at 50 °C for 3 h, then put into a pulverizer for pulverization, and sieved through 2000 meshes to obtain the insulating modified expandable graphite.

[0042] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 lies in that the dosages of raw materials and process parameters are different, as shown in Table 1 specifically; Table 1 Dosages (%) of raw materials and reaction time and temperature of Preparation Examples 1-3 are different Preparation of Comparative Examples Preparation of Comparative Example 1 The difference between Preparation of Comparative Example 1 and Preparation Example 1 lies in that 2,3'-diallylbisphenol A was equally replaced with organosilicon-modified polyurethane emulsion.

[0043] Preparation of Comparative Example 2 The difference between Preparation of Comparative Example 2 and Preparation Example 1 lies in that methacryloylethylsulfobetaine was equally replaced with glycidoxypropylcyclotetrasiloxane.

[0044] Preparation of Comparative Example 3 The difference between Preparation of Comparative Example 3 and Preparation Example 1 lies in that the acryloyloxy group-containing silane is 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane.

[0045] Preparation Examples of Silicone Rubber Materials Preparation Example 4 A silicone rubber material was prepared by the following method: Weigh 1% acryloxy silane and 0.1% expandable graphite according to the weight percentage of the silicone rubber material, and mix them evenly to obtain mixture A; weigh 48% vinyl raw rubber, 5% hydrogen-containing silicone oil, and 20% hydroxy silicone oil, put them into a kneader, and mix them at a rotation speed of 100 r / min for 30 min to make them evenly mixed. Then start heating, add 23% white carbon black, and continue stirring to make them evenly mixed. When the temperature reaches 130 °C, stop heating, and react at 130 °C for 30 min. Then add all of mixture A, continue stirring for 30 min to make them evenly mixed, heat to 160 °C, keep the temperature for reaction for 2 h, cool to 45 °C, then put it into a two-roll rubber mill for rubber mixing, and then put it into a rubber filtering device for filtering to obtain a mixed rubber; add 2.9% vulcanizing agent to the mixed rubber and mix it to make the vulcanizing agent evenly dispersed in the mixed rubber to obtain the silicone rubber material.

[0046] Preparation Example 5-6 The differences between Preparation Example 5-6 and Preparation Example 1 are as follows: the raw material dosages and processes are different, as shown in Table 2 specifically; Table 2 Raw Material Dosages and Processes of Preparation Examples 4-6 Preparation Examples 7-12 The differences between Preparation Examples 7-12 and Preparation Example 5 are as follows: the expandable graphite is insulating modified expandable graphite, and the sources of the insulating modified expandable graphite are different, as shown in Table 2 specifically; Sources of Insulating Modified Expandable Graphite in Preparation Examples 7-12 Test item Source of insulating modified expandable graphite Preparation Example 7 Preparation Example 1 Preparation Example 8 Preparation Example 2 Preparation Example 9 Preparation Example 3 Preparation Example 10 Preparation Comparative Example 1 Preparation Example 11 Preparation Comparative Example 2 Preparation Example 12 Preparation Comparative Example 3 Preparation of Comparative Examples Preparation of Comparative Example 4 The difference between Preparation of Comparative Example 4 and Preparation Example 4 is that the acryloxy silane is replaced with vinyl raw rubber in equal amounts.

[0047] Preparation of Comparative Example 5 The difference between Preparation of Comparative Example 5 and Preparation Example 4 is that the expandable graphite is replaced with carbon black in equal amounts.

[0048] Preparation of Comparative Example 6 The difference between Preparation of Comparative Example 6 and Preparation Example 4 is that both the acryloxy silane and the expandable graphite are replaced with vinyl raw rubber in equal amounts. Examples

[0049] Example 1 This example provides a high-sealing shock-absorbing aluminum electrolytic capacitor, referring to Figures 1-2, including an aluminum shell 1, an element 2, a sealing plug 3 and a cushion 4. The element 2 is accommodated inside the aluminum shell 1. The sealing plug 3 seals the element 2 in the aluminum shell 1. A terminal 211 is provided at the end of the element 2 and extends along the length direction. The sealing plug 3 is provided with a first through hole 31 for the lead wire 21 to pass through. The lead wire 21 extends and is provided with a terminal 211, and the terminal 211 extends to the outer surface of the seal. The cushion 4 is installed at the opening of the aluminum shell 1 and abuts against the sealing plug 3. The cushion 4 is provided with a second through hole 41 for the terminal 211 to pass through. Both the sealing plug 3 and the cushion 4 are made of silicone rubber material.

[0050] The first electrolytic paper 22 abuts against the inner wall of the aluminum shell 1. One lead wire 21 is located between the anode foil 23 and the second electrolytic paper 24, and this lead wire 21 is the anode lead wire 21; the other lead wire 21 is located between the cathode foil 25 and the first electrolytic paper 22, and this lead wire 21 is the anode lead wire.

[0051] The element 2 is sequentially provided with a first electrolytic paper 22, an anode foil 23, a second electrolytic paper 24 and a cathode foil 25 from the outer layer to the inner layer. During the winding process of the first electrolytic paper 22, the anode foil 23, the second electrolytic paper 24 and the cathode foil 25, the lead wire 21 is coated to form the element 2. The first electrolytic paper 22 abuts against the inner wall of the aluminum shell 1. One lead wire 21 is the anode lead wire 21 and is located between the anode foil 23 and the second electrolytic paper 24; the other lead wire 21 is the cathode lead wire 21 and is located between the cathode foil 25 and the first electrolytic paper 22.

[0052] The element 2 further includes an electrolyte, and the electrolyte adheres to the surfaces of the first electrolytic paper 22, the anode foil 23, the second electrolytic paper 24, the cathode foil 25 and the lead wire 21. The electrolyte of this application is preferably a high-temperature resistant electrolyte, which is mainly composed of components such as ethylene glycol, polyethylene glycol, ammonium 1,7-decanedioate, ammonium adipate, ammonium dodecanedioate, ammonium benzoate, mannitol, ammonium hypophosphite, p-nitrobenzoic acid and p-nitrobenzyl alcohol. With the above raw materials and compositions, combined with the use of silicone rubber materials for the sealing plug and the cushion in this application, a better-structured, high-temperature resistant, highly sealed and shock-absorbing aluminum electrolytic capacitor is obtained.

[0053] Example 2 The difference between Example 2 and Example 1 is that this highly sealed and shock-absorbing aluminum electrolytic capacitor is prepared by the following method: Step 1: Stack the first electrolytic paper, the anode foil, the second electrolytic paper and the cathode foil in sequence and wind them. During the winding process, wind the lead wire, as Figure 4 shown, and then impregnate with the electrolyte for 10 minutes, as Figure 3 shown, to obtain the element; put the silicone rubber material obtained in Preparation Example 1 into a mold, and then carry out vulcanization molding at a temperature of 150 °C and a vulcanization time of 5 minutes to obtain the sealing plug and the cushion.

[0054] Step 2: Place the element in the aluminum shell, then plug the opening of the aluminum shell with a sealing plug, and the lead wire in the element passes through the first through hole of the sealing plug, so that the element is sealed inside the aluminum shell. Install a cushion on the opening of the aluminum shell, so that the sealing plug is sealed inside the aluminum shell, and the terminal extended from the lead wire passes through the cushion to obtain a highly sealed shock-absorbing aluminum electrolytic capacitor.

[0055] Example 3 The difference between Example 3 and Example 2 is that: in Step 2, a thermal expansion treatment is also included, specifically as follows: Place the element in the aluminum shell, then push the sealing plug into the aluminum shell and position it at the opening of the aluminum shell. The inner wall of the aluminum shell abuts against the sealing plug and the lead wire in the element passes through the first through hole of the sealing plug, so that the element is stably sealed to prevent water ingress, etc. Install a cushion on the outer wall of the opening of the aluminum shell, and seal the sealing plug on the inner wall of the aluminum shell, and the terminal extended from the lead wire passes through the cushion, so that the cushion protects the terminal to obtain a capacitor. Perform thermal expansion at 210 °C for 1 s, so that the expandable graphite expands slightly at this temperature. Due to the short heating time, only slight expansion occurs, and both the sealing plug and the cushion play a better sealing and buffering effect to obtain a highly sealed shock-absorbing aluminum electrolytic capacitor.

[0056] Examples 4 - 14 The difference between Examples 4 - 14 and Example 3 is that: the sources of the silicone rubber materials are different, as shown in Table 3 specifically; Table 3 Sources of silicone rubber materials for Examples 3 - 14 Example Silicone rubber material Example 3 Preparation Example 4 Example 4 Preparation Example 5 Example 5 Preparation Example 6 Example 6 Preparation Example 7 Example 7 Preparation Example 8 Example 8 Preparation Example 9 Example 9 Preparation Example 10 Example 10 Preparation Example 11 Example 11 Preparation Example 12 Example 12 Preparation Comparative Example 4 Example 13 Preparation Comparative Example 5 Example 14 Preparation Comparative Example 6 Comparative Example Comparative Example 1 The difference between the comparative example and Example 2 is that: there is no cushion.

[0057] Performance detection test The specifications of the aluminum electrolytic capacitors obtained in Examples 2 - 14 and Comparative Example 1 are as follows: The diameter of the element is 2 cm; the thickness of the aluminum shell is 1 mm, and the total length is 3.8 cm; the sealing plug has a diameter of 2.0 cm and a height of 0.8 cm. One side of the cushion close to the aluminum shell is in close contact with the sealing plug. The thickness from the side of the cushion far from the sealing plug to the side close to the sealing plug is 0.4 cm, and the thickness of the side of the cushion in close contact with the outer surface of the aluminum shell is 0.3 cm, and the contact length is 0.3 cm.

[0058] Detection method / test method Experiment (1) Test 1: Double 85 test. The aluminum electrolytic capacitors obtained in Examples 2 - 14 and Comparative Example 1 were placed in an environment with a temperature of 85% and a humidity of 85%, and were respectively tested for 1000 h, 1200 h, and 1500 h. After taking them out, air-drying them, and then powering them on, it was tested and inspected whether the capacitors could be used normally. If they could not be used normally, the test time was recorded. If they could still be used normally after more than 1500 h, it was recorded as more than 1500 h.

[0059] Test 2: Shock buffer test. The aluminum electrolytic capacitors obtained in Examples 2 - 14 and Comparative Example 1 were made to free fall from a 2 - mm high platform, with the length direction of their shells parallel to the ground. It was checked whether there were phenomena such as electrolyte leakage (referring to leakage through the sealing plug), cushion or piston detachment, and lead wire breakage, and it was also tested and inspected whether the capacitors could be used normally by powering them on. It was repeated 5 times, 10 times, and 20 times respectively. If the above phenomena (could not be used normally, electrolyte leakage, lead wire breakage, cushion or piston detachment) occurred, the corresponding number of times was recorded. When the number of times was more than 20 times, it was recorded as more than 20 times.

[0060] The above experimental data are specifically shown in Table 4 as follows; Table 4 Experimental data of Examples 2 - 14 and Comparative Example 1 Test item Test 1 Test 2 (times) Example 2 1200 20 Example 3 1500 Greater than 20 Example 4 1500 Greater than 20 Example 5 1500 Greater than 20 Example 6 Greater than 1500 Greater than 20 Example 7 Greater than 1500 Greater than 20 Example 8 Greater than 1500 Greater than 20 Example 9 1500 Greater than 20 Example 10 1500 Greater than 20 Example 11 1500 Greater than 20 Example 12 1500 Greater than 20 Example 13 1500 10 times Example 14 1500 10 times Comparative Example 1 1000 Unqualified It can be seen from the above table that both the double 85 test and the shock buffer test of Examples 2 - 13 are better than those of Comparative Example 1, indicating that by setting the cushion in this application, it can cooperate with the piston to further improve the buffer performance and sealing performance, and thus improve the structural stability of the aluminum electrolytic capacitor. And the number of times of the shock buffer test and the double 85 test time of Example 3 are greater than those of Example 2, indicating that within the specific temperature and time of this application, thermal expansion treatment is carried out on it to improve the tightness of its structural connection, especially the tightness of the connection between the cushion, the sealing plug, and the aluminum shell, as well as the tightness of the cushion, the sealing plug and the lead wire, and reduce the occurrence of phenomena such as electrolyte leakage and water ingress. And the number of times of the shock buffer test and the double 85 test time of Example 6 are greater than those of Example 4, indicating that through the insulating modified expandable graphite with better performance, combined with the production process of this application, it can further improve the tightness of its structural connection, so as to obtain a high - sealing and shock - absorbing aluminum electrolytic capacitor.

[0061] Experiment Two: The silicone rubber materials in Examples 3 - 13 were put into a mold, and then put into a vulcanizer. At 150 °C, vulcanization was carried out for 5 min. After taking it out, it was cooled to 40 °C and demolded. The obtained test samples were subjected to the following performance tests: tensile strength and elongation at break tests according to the reference test method ASTM D412. The thickness of the test samples was 1.5 mm.

[0062] The above data are specifically shown in Table 5 as follows; Experimental data of silicone rubber materials in Examples 3 - 13 in Table 5 Test item Tensile strength (MPa) Elongation at break (%) Example 3 33 415 Example 4 34 411 Example 5 33 418 Example 6 41 450 Example 7 42 448 Example 8 40 455 Example 9 37 432 Example 10 38 434 Example 11 37 439 Example 12 28 411 Example 13 30 402 Example 14 26 405 Combined with Examples 3, 6, 9 - 14 and Table 5, it can be seen that the tensile strength and elongation at break of Examples 3, 9 - 14 are lower than those of Example 6, indicating that the insulation - modified expandable graphite prepared in this application, when used in the raw material system of the silicone rubber material of this application, can cooperate with its raw material system to further improve its comprehensive performance. Therefore, when used in the production of electrolytic capacitor sealing plugs and cushions, it can achieve a better buffering and sealing effect, further improving the durability of electrolytic capacitors in extreme environments.

[0063] This specific embodiment is only an interpretation of this application, and it is not a limitation of this application. After reading this specification, those skilled in the art can make modifications to this embodiment that do not contribute creatively according to needs, but as long as they are within the scope of the claims of this application, they are protected by the patent law.

Claims

1. A high-sealing shock-absorbing aluminum electrolytic capacitor, characterized in that: The invention comprises an aluminum shell (1), an element (2), a sealing plug (3) and a cushion (4), wherein the element (2) is accommodated inside the aluminum shell (1), the sealing plug (3) seals the element (2) in the aluminum shell (1), two leads (21) are extended from the end of the element (2), the sealing plug (3) is provided with a first through hole (31) for each lead (21) to pass through, each lead (21) is extended with a terminal (211), and the terminal (211) extends to the outer surface of the sealing member, the cushion (4) is installed at the opening of the aluminum shell (1) and seals the sealing plug (3), the cushion (4) is provided with a second through hole (41) for the terminal (211) to pass through, and the sealing plug (3) and the cushion (4) are both made of silicone rubber material.

2. The high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 1, characterized in that: The element (2) is provided with a first electrolytic paper (22), an anode foil (23), a second electrolytic paper (24) and a cathode foil (25) in sequence from the outer layer to the inner layer. The first electrolytic paper (22), the anode foil (23), the second electrolytic paper (24) and the cathode foil (25) wrap the lead wire (21) during the winding process to form the element (2). The first electrolytic paper (22) abuts against the inner wall of the aluminum shell (1). One of the lead wires (21) is located between the anode foil (23) and the second electrolytic paper (24), and the other lead wire (21) is located between the cathode foil (25) and the first electrolytic paper (22).

3. The high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 1, characterized in that: The element (2) further comprises an electrolyte, wherein the electrolyte is attached to the surfaces of the first electrolytic paper (22), the anode foil (23), the second electrolytic paper (24), the cathode foil (25), and the lead wire (21).

4. The high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 1, characterized in that: The silicone rubber material is composed of the following raw materials in percentage by weight: Vinyl rubber 48-62% Hydrogen silicone oil 5-8% Hydroxyl silicone oil 10-20% Contains 1-5% acryloxysilane White carbon black 10-23% Expandable graphite 0.5-2.3% The balance is the vulcanizing agent.

5. The high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 1, characterized in that: The acryloxy group-containing silane is composed of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and (3-acryloxypropyl)tris(trimethylsiloxy)silane.

6. The high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 1, characterized in that: The expandable graphite is an insulating modified expandable graphite, and the insulating modified expandable graphite is composed of the following raw materials in percentage by weight: Silicone modified polyurethane emulsion 5-8% Expandable graphite 40-65% Benzoyl peroxide 0.1-0.5% 2,3'-Diallyl bisphenol A 0.1-1.3% Glycidyl ether oxypropyl cyclotetrasiloxane 1-3% Methacryloylethyl sulfobetaine 0.1-0.8% The balance is diethylene glycol methyl ethyl ether.

7. A high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 6, characterized in that: The insulating modified expandable graphite is prepared by the following method: According to weight percentage, benzoyl peroxide, 2,3'-diallyl bisphenol A, glycidyloxypropyl cyclotetrasiloxane, methacryloylethyl sulfobetaine, and diethylene glycol methyl ethyl ether are mixed evenly, added to 60-68° C., reacted for 1-2 hours, then added with silicone-modified polyurethane emulsion, mixed evenly, then added with expandable graphite, mixed evenly, distilled under reduced pressure, the solvent was removed, dried, crushed, and sieved to obtain insulating modified expandable graphite.

8. A high-sealing shock-absorbing aluminum electrolytic capacitor according to any one of claims 1 to 7, characterized in that: The silicone rubber material is prepared by the following method: According to the weight percentage, acryloxy silane and expandable graphite are weighed and mixed evenly to obtain a mixture A; vinyl raw rubber, hydrogen silicone oil and hydroxy silicone oil are weighed and mixed evenly, heating is started, white carbon black is added, mixed evenly, heated to 125-135°C for reaction for 20-30min, and then the mixture A is added, mixed evenly, heated to 150-165°C, reacted for 2-4h, cooled to 45-55°C, rubber mixed, filtered, and a mixed rubber is obtained; a vulcanizing agent is added to the mixed rubber, mixed, and the vulcanizing agent is evenly dispersed in the mixed rubber to obtain a silicone rubber material.

9. A production process for a high-sealing shock-absorbing aluminum electrolytic capacitor according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: stack the first electrolytic paper, anode foil, second electrolytic paper, and cathode foil in sequence, and wind them. During the winding process, the lead wire is wound, and then impregnated with electrolyte to obtain the element; put the silicone rubber material into a mold, and then vulcanize and mold it to obtain a sealing plug and a cushion; Step 2: Place the element in an aluminum shell, and then seal the aluminum shell with a sealing plug, and pass the lead wire in the element through the first through hole of the sealing plug to seal the element, install a cushion at the opening of the aluminum shell, seal the sealing plug inside the aluminum shell, and pass the terminal extending from the lead wire through the cushion to obtain a highly sealed shock-absorbing aluminum electrolytic capacitor.

10. The production process of a high-sealing shock-absorbing aluminum electrolytic capacitor according to claim 9, characterized in that: The step 2 also includes performing a thermal expansion treatment, which is specifically as follows: The element is placed in an aluminum shell, and then a sealing plug is used to seal the aluminum shell, and the lead wire in the element passes through the first through hole of the sealing plug to seal the element, and a cushion is installed at the opening of the aluminum shell, so that the sealing plug is sealed inside the aluminum shell, and the terminal extending from the lead wire passes through the cushion to obtain a capacitor, and thermal expansion is carried out at 200-210°C for 0.1-1s to obtain a high-sealing shock-absorbing aluminum electrolytic capacitor.